The Association between Non-Alcoholic Fatty Liver Disease and Cardiovascular Risk in Children - Anna Di Sessa; Giuseppina Rosaria Umano; Emanuele Miraglia del Giudice (MDPI AG, 2017)
The rising prevalence of childhood obesity in the past decades has made Non-Alcoholic Fatty Liver Disease (NAFLD) the most common cause of pediatric chronic liver disease worldwide. Currently, a growing body of evidence links NAFLD with cardiovascular disease (CVD) even at an early age. Data on the pediatric population have shown that NAFLD could represent an independent risk factor not only for cardiovascular events but also for early subclinical abnormalities in myocardial structure and function. Briefly, we review the current knowledge regarding the relationship between pediatric NAFLD and cardiovascular risk in an attempt to clarify our understanding of NAFLD as a possible cardiovascular risk factor in childhood.